HUBUNGAN ANTARA KECERDASAN EMOSI DENGAN KINERJA GURU MTS ATTAQWA KOTA TANGERANG - Shofi Shofuroh; Bambang S. Arifin; Irfan Fahmi (Psympathic : Jurnal Ilmiah Psikologi, 2012)
This research based on the phenomena that some teachers have not done their job effectively and efficiently. It is expected that emotional intelegence has correlation with that phenomena. Emotional intelegence is an individual ability to know their own emotion, manage the emotion, motivate themselves, have emphaty and skill in relationship. Some aspects in emotional intelegence expected have correlation with performance. Population are teachers MTs At Taqwa Tangerang who are actively doing the teaching and learning process. This research used quantitative methodology with correlational analysis. Subjects are 100 teachers. Result shows that thitung  is more than ttabel. Therefore, H0 is not accepted and H1 is accepted so that there is positive correlation between emotional intelegence and teachers performance at MTs At Taqwa Tangerang.